Diastereoselective addition of planar N-heterocycles to vinyl sulfone-modified carbohydrates: a new route to isonucleosides - Sanki, Aditya K.; Bhattacharya, Rahul; Atta, Ananta Kumar; Suresh, Cheravakkattu G.; Pathak, Tanmaya (Tetrahedron, 2008)
Michael-type addition reactions of planar N-heterocycles at the C-2 positions of vinyl sulfone-modified carbohydrates provide an efficient and general route for the carbon-N-heterocycle bond formation. Therefore, the addition pattern of planar heterocycles, such as imidazole, triazole, thymine, and adenine to 3-C-phenyisulfonyl-hex-2-enopyranosides (1 alpha/1 beta) and 3-C-p-toluenesulfonyl-pent-2-enofuranosides (2 alpha/2 beta) was studied for developing a general methodology for the synthesis of new classes of isonucleosides possessing a carbon-N-heterocycle linkage at C-2 positions of furanosyl and pyranosyl sugars. To a great extent, the anomeric configurations of the starting vinyl sulfones play crucial roles in deciding the diastereoselectivity of addition of heterocycles. However, the trityl protected 3-C-p-toluenesulfonyl-hex-2-enopyranosides (33 alpha/33 beta) were judged to be More practical starting materials for desulfortylation and deprotection for the synthesis of a new class of thymine and adenine deoxyisonucleosides. (C) 2008 Elsevier Ltd. All rights reserved.